2010
DOI: 10.1152/japplphysiol.00966.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ultraendurance exercise increases the production of reactive oxygen species in isolated mitochondria from human skeletal muscle

Abstract: Exercise-induced oxidative stress is important for the muscular adaptation to training but may also cause muscle damage. We hypothesized that prolonged exercise would increase mitochondrial production of reactive oxygen species (ROS) measured in vitro and that this correlates with oxidative damage. Eight male athletes (24-32 yr) performed ultraendurance exercise (kayaking/running/cycling) with an average work intensity of 55% V(O(2peak)) for 24 h. Muscle biopsies were taken from vastus lateralis before exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 48 publications
6
62
0
Order By: Relevance
“…The influence of physical exercise regularity on TAC concentrations was tested. After consecutive days of exercise training a progressive decreasing on oxidative stress was observed, whereas the TAC remained at higher levels (Sahlin et al 2010). Although ultraendurance exercise had increased ROS production in isolated mitochondria this effect was abolished after 28 h and no mitochondrial protein damage was observed (Shing et al 2007).…”
Section: Regular Physical Exercise: Adaptation To Oxidative Stress Anmentioning
confidence: 98%
“…The influence of physical exercise regularity on TAC concentrations was tested. After consecutive days of exercise training a progressive decreasing on oxidative stress was observed, whereas the TAC remained at higher levels (Sahlin et al 2010). Although ultraendurance exercise had increased ROS production in isolated mitochondria this effect was abolished after 28 h and no mitochondrial protein damage was observed (Shing et al 2007).…”
Section: Regular Physical Exercise: Adaptation To Oxidative Stress Anmentioning
confidence: 98%
“…Severe exercise intensities activate a cascade of intracellular sources for reactive oxygen species (ROS) and it is clear that muscle adaptation depends on this process. However, it is important to observe that excessive ROS production can negatively influence exercise performance and can also lead to long-term health consequences (Bailey et al, 2004;Sahlin et al, 2010;Sun et al, 2010). The mechanism of increased ROS production during exercise is not totally clear, but experimental evidence suggests that mitochondria are the main source of ROS production during exercise (Di Meo & Venditti, 2001;Fernstrom et al, 2007).…”
Section: Mitochondrial Proteomics Applied To Exercise Researchmentioning
confidence: 99%
“…The first evidence that exercise induced increases in RONS came from electron spin resonance data [20,48]. Further studies demonstrated that active skeletal muscles released nitric oxide [7], hydroxyl radicals [84], superoxide anions [70] and hydrogen peroxide [71], but only recently it was incontrovertibly demonstrated that mitochondria are the major biological source of ROS production during physical exercise [93]. In fact, there are a number of possible intracellular sources for ROS beside mitochondria, including cytochrome P450, myeloperoxidase, xanthine oxidase, NADH oxidase and peroxisomal oxidative enzymes, all of which may be substantially increased upon exercise.…”
Section: Exercise and Generation Of Reactive Oxygen Andmentioning
confidence: 99%